2015
DOI: 10.1074/jbc.r114.619957
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Adipocyte Differentiation: A Central Role for CCAAT/Enhancer-binding Protein (C/EBP) β

Abstract: A detailed understanding of the processes controlling adipogenesis is instrumental in the fight against the obesity epidemic. Adipogenesis is controlled by a transcriptional cascade composed of a large number of transcriptional factors, among which CCAAT/enhancer-binding protein (C/EBP) ␤ plays an essential role. During 3T3-L1 adipocyte differentiation, C/EBP␤ is induced early to transactivate the expression of C/EBP␣ and peroxisome proliferator-activated receptor ␥ (PPAR␥), two master transcription factors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
230
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(246 citation statements)
references
References 71 publications
5
230
1
1
Order By: Relevance
“…3). C/EBPa plays a very important role during adipocyte terminal differentiation [14]. In the present study, its expression was reduced by WAY-262611 and LiCl (Fig.…”
Section: Wnt/b-catenin Pathway Inhibits Adipogenic Transcription Pattmentioning
confidence: 80%
“…3). C/EBPa plays a very important role during adipocyte terminal differentiation [14]. In the present study, its expression was reduced by WAY-262611 and LiCl (Fig.…”
Section: Wnt/b-catenin Pathway Inhibits Adipogenic Transcription Pattmentioning
confidence: 80%
“…After hormonal induction, a rapid and transient increase in transcription and expression of C/EBP␤ and C/EBP␦ is observed in preadipocytes that activates the expression of PPAR␥ and C/EBP␣ (56). The activation of C/EBP␣ is followed by transcriptional activation of many genes encoding proteins involved in creating the adipocyte phenotype (GLUT4, SCD1, LEP, FABP4) (110). C/EBP, a dominant inhibitor of C/EBP␣ and -␤, is induced in late adipocyte differentiation and has been proposed as an inhibitor of adipogenesis.…”
Section: Ontogeny and Function Of White Brown And Beige Adipose Tissuementioning
confidence: 99%
“…25) We previously reported that FAD24 acted in concert with HBO1 to promote MCE by controlling DNA replication. 7) In this study, we showed that fad24 is a positive regulator of S phase re-entry of quiescent C2C12 myoblasts.…”
Section: Discussionmentioning
confidence: 99%